2022
DOI: 10.1039/d2ob00551d
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization-specific chemical reactions to create interstrand crosslinking and threaded structures of nucleic acids

Abstract: The interstrand crosslinking and threaded structures of nucleic acids have high potential in oligonucleotide therapeutics, chemical biology, and nanotechnology. For example, properly designed crosslinking structures provide high activity and nuclease...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…In nucleic acid chemistry, interlocked and threaded molecular structures have been studied for DNA nanotechnology, topological labeling, , and complex stabilization. , Since nucleic acids are substrates for ligases, ligase reactions enabled the formation of numerous interlocked structures. Further, template-assisted chemical strand ligations via [2 + 2] photocyclization, , amidation, and click reaction ,, have been used to expand the applications of interlocked nucleic acids …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In nucleic acid chemistry, interlocked and threaded molecular structures have been studied for DNA nanotechnology, topological labeling, , and complex stabilization. , Since nucleic acids are substrates for ligases, ligase reactions enabled the formation of numerous interlocked structures. Further, template-assisted chemical strand ligations via [2 + 2] photocyclization, , amidation, and click reaction ,, have been used to expand the applications of interlocked nucleic acids …”
Section: Introductionmentioning
confidence: 99%
“…Further, template-assisted chemical strand ligations 50 via [2 + 2] photocyclization, 51,52 amidation, 53 and click reaction 33,54,55 have been used to expand the applications of interlocked nucleic acids. 56 Following these studies, we previously developed automatic pseudorotaxane-forming oligo DNAs with reactive moieties for S N 2 and strain-promoted azide−alkyne cycloaddition (SPAAC) reactions. 57,58 Additionally, we found that the chemically cyclized oligodeoxynucleotides (cyODNs) with a double tail formed a pseudorotaxane structure with the target DNA and RNA via the slipping process (Figure 1).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1−4 The formation of a covalent bond between correctly oriented functional groups in single strands leads to the formation of an interstrand crosslink (ICL). 5 ICLs are of interest in biology because they inhibit replication and transcription, leading to cellular toxicity. 6 Examples of small-molecule-induced ICL are formed by anticancer drugs such as cisplatin 7 and nitrogen mustards.…”
mentioning
confidence: 99%
“…The DNA double helix is an outstanding scaffold for the guided arrangement of functional groups. Precise control of chromophores or reactive groups in DNA can lead to functional materials that offer new opportunities for chemical biology and nanotechnology. The formation of a covalent bond between correctly oriented functional groups in single strands leads to the formation of an interstrand crosslink (ICL) . ICLs are of interest in biology because they inhibit replication and transcription, leading to cellular toxicity .…”
mentioning
confidence: 99%